2009
DOI: 10.3174/ajnr.a1693
|View full text |Cite
|
Sign up to set email alerts
|

Association of White Matter Hyperintensity Measurements on Brain MR Imaging with Cognitive Status, Medial Temporal Atrophy, and Cardiovascular Risk Factors

Abstract: BACKGROUND AND PURPOSE:White matter hyperintensities (WMHs) are frequently characterized as markers of cerebrovascular disease, whereas medial temporal atrophy (MTA) is a recognized marker of Alzheimer disease (AD). Our purpose was to test the reliability of a visual rating system (VRS) in evaluating WMHs and MTA and in distinguishing healthy from cognitively impaired subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
2
34
2
Order By: Relevance
“…AD and amnesic MCI are associated with an increased volume of WM lesions compared to healthy controls 56,57 , which predicts the rate of cognitive decline. 58 We did not find a significant effect of the APOE ε4 allele and this is in concordance with two studies reporting an effect of APOE genotype on volume of WM lesions only for homozygous individuals and no gene-dose effect.…”
Section: Effect Of Apoe Genotype On Wmmentioning
confidence: 99%
“…AD and amnesic MCI are associated with an increased volume of WM lesions compared to healthy controls 56,57 , which predicts the rate of cognitive decline. 58 We did not find a significant effect of the APOE ε4 allele and this is in concordance with two studies reporting an effect of APOE genotype on volume of WM lesions only for homozygous individuals and no gene-dose effect.…”
Section: Effect Of Apoe Genotype On Wmmentioning
confidence: 99%
“…[1][2][3] Such common brain changes include global atrophy, white matter injury, smallvessel ischemia, and microhemorrhages. [4][5][6][7][8] These changes are more frequent and more severe in neurodegenerative and neurovascular conditions such as Alzheimer disease (AD), than in healthy aging.…”
mentioning
confidence: 99%
“…However, we could not verify the high ability of the rWTH to distinguish MCI from HCs in our study population using conventional axial FLAIR images. Another study group found good correlation of WMH scores and medial temporal atrophy, which were both increased in subjects with probable AD compared to cognitively unimpaired and naMCI subjects (27).…”
Section: Discussionmentioning
confidence: 97%
“…WMHs on FLAIR images are a common finding among elderly cognitively healthy subjects, in those with MCI and a variety of dementias (27). The appearance of WMHs is attributed to processes of normal aging, cerebrovascular disease, and neurodegenerative processes, such as gliosis, microglial infiltration, and amyloid angiopathy (28).…”
Section: Discussionmentioning
confidence: 99%